Clinicopathologic analysis of lethal influenza cases in 2009–2011 - S. A. Gladkov; I. V. Grigorieva; V. A. Dedov; E. V. Esaulenko; V. A. Zinserling (Журнал инфектологии, 2014)
The authors conducted clinicopathologic analysis of 33 cases of lethal influenza caused mainly by influenza virus H1N1/California in northwest regions of Russia. Five types of structural changes in lungs were outlined: 1) massive serous-hemorrhagic edema (9% of studied cases); 2) serous and desquamative viral pneumonia (6%); 3) viral pneumonia with acute phase of diffuse alveolar damage (DAD) (18%); 4)viral pneumonia with prevalence of regenerative and hyperplastic changes (27%); 5) mixed viral and bacterial pneumonia (36%). The authors also made morphological description of two types of virus-induced cytopathic changes (two types of «influenza»-cells).